Changing Trends in the Etiology of Cirrhosis in Türkiye: A Multicenter Nationwide Study - Üçbilek, Enver; Yıldırım, Abdullah Emre; Ellik, Zeynep; Turan, İlker; Haktanıyan, Büşra; Orucu, Berk; Demir, Mehmet; Tozlu, Mukaddes; Yılmaz, Nimet; Balaban, Yasemin; Uyanıkoğlu, Ahmet; Akarsu, Mesut; et al. (Turkish Journal of Gastroenterology, 2024)
Background/Aims: The aim of our study was to investigate the underlying causes behind the etiology of cirrhosis in Türkiye. Materials and Methods: The study was comprised of patients with cirrhosis located in the gastroenterology clinics of 28 centers in Türkiye between January 2000 and June 2021. Results: The study group consisted of 4953 cirrhotic patients (median age: 62.2 years, male / female: 58% / 42%). Among the patients, 39% of the patients were compensated, and 61% were decompensated. Furthermore, 47.5% had Child-Pugh class A, 38% had ChildPugh class B, and 14.5% had Child-Pugh class C. The most frequent complaints were abdominal bloating (28%). Ascites (54.2%) was the most common manifestation of decompensation. The median Child-Pugh and MELD-Na scores were 7.0 and 10.0, respectively. The most common cause of cirrhosis was chronic viral hepatitis (43%), followed by cryptogenic cirrhosis (CC) (19%), metabolic dysfunction-associated steatotic liver disease (MASLD)-related cirrhosis (13%), and alcohol-related cirrhosis (11%). Among the 950 patients with CC, 416 had metabolic abnormalities. If these 416 CC patients with metabolic abnormalities were categorized as having MASLDrelated cirrhosis, the proportion of MASLD-related cirrhosis increased to 21%. Thirteen percent of the patients were diagnosed with HCC, while 4% had extrahepatic malignancy. Female breast cancer (18%) and colorectal cancer (18%) were the most frequent extrahepatic malignancies. Conclusion: Viral hepatitis remains the main cause of cirrhosis in Türkiye. However, its prevalence seems to be declining, whereas the prevalence of steatotic liver disease-related cirrhosis is increasing. Cite this article as: Üçbilek E, Yıldırım AE, Ellik Z, et al. Changing trends in the etiology of cirrhosis in Türkiye: A multicenter nationwide study. Turk J Gastroenterol. 2024;35(10):772-777.